Ternary positive electrode material and preparation method thereof, and electrochemical device
The formation of a cladding layer containing lithium phosphate through a step-by-step wet spray coating process, solving the problem of structural changes and capacity attenuation of the ternary positive electrode material in lithium-ion batteries, and significantly improving the rate performance and cycle stability of the material.
Patent Information
- Application Number
- CN202411618157.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The ternary positive electrode material has problems of structural changes and capacity attenuation in lithium-ion battery applications, which limits its rate performance and cycle life.
A step-by-step wet spray coating process is adopted to form an inner cladding layer of lithium hydroxide, then form an outer cladding layer of phosphate, and a cladding layer containing lithium phosphate is formed during the secondary sintering process. The concentration gradient of lithium ions in the cladding layer gradually increases from the outside to the inside in the radial direction.
The rate performance and cycle stability of the ternary positive electrode material are improved, structural stability and thermal stability are enhanced, the transmission efficiency of lithium ions is optimized, and structural damage caused by stress concentration is reduced.
Smart Images

Figure CN119284976B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new energy materials, and in particular to a ternary positive electrode material and a preparation method thereof, and an electrochemical device. Background Art
[0002] Ternary cathode materials mainly refer to composite oxides containing nickel (Ni), cobalt (Co), manganese (Mn) or aluminum (Al), such as lithium nickel cobalt manganese oxide or lithium nickel cobalt aluminum oxide, which are important cathode materials in lithium-ion batteries. Due to their high energy density and good stability, ternary cathode materials have become a hot topic in current research and application.
[0003] However, there are some defects in the application of ternary cathode materials in lithium-ion batteries, which limit their rate performance and cycle life, such as easy structural changes and capacity decay. Therefore, how to improve the structural stability and capacity of ternary cathode materials is the main problem facing ternary cathode materials at present. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a ternary positive electrode material.
[0005] The embodiments of the present application provide a ternary positive electrode material prepared by the aforementioned method for preparing the ternary positive electrode material, and an electrochemical device using the ternary positive electrode material.
[0006] The present application also provides a method for preparing a ternary positive electrode material, comprising:
[0007] The ternary cathode material precursor is mixed with a lithium source and sintered once to obtain a core;
[0008] The inner core is mixed with a lithium hydroxide solution by spray coating to obtain a first mixture having an inner lithium hydroxide coating layer;
[0009] Mixing the first mixture with a phosphoric acid solution by spray coating to obtain a second mixture having an outer coating layer of phosphoric acid; and
[0010] The second mixture is sintered for a second time to form a coating layer containing lithium phosphate on the surface of the inner core to obtain the ternary positive electrode material, wherein the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer.
[0011] In some possible embodiments, the mass ratio of lithium hydroxide to the core in the lithium hydroxide solution is (0.001-0.02):1.
[0012] In some possible embodiments, the mass ratio of phosphoric acid in the phosphoric acid solution to the core is (0.001-0.02): 1;
[0013] The molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is (0.78-2.1):3.
[0014] In some possible embodiments, in the step of performing secondary sintering on the second mixture, the secondary sintering temperature is 300° C. to 500° C., and the sintering time is 6 h to 18 h.
[0015] In some possible embodiments, the step of preparing the first mixture further includes:
[0016] The first mixture having the lithium hydroxide inner coating layer is dried at a temperature of 150° C. to 250° C. and for a time of 0.5 h to 1 h.
[0017] In some possible embodiments, the chemical formula of the ternary cathode material precursor is LiNi x Co y Mn 1-x-y (OH) 2 , where 0.5≤x≤0.7, 0≤y≤0.1.
[0018] An embodiment of the present application also provides a ternary positive electrode material, which is prepared by the aforementioned method for preparing the ternary positive electrode material. The ternary positive electrode material includes an inner core and a coating layer located on the surface of the inner core, wherein the inner core is a ternary positive electrode active material, the coating layer contains lithium phosphate, and the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer.
[0019] In some possible embodiments, the coating layer has a thickness of 3 nm to 10 nm.
[0020] In some possible embodiments, the chemical formula of the ternary positive electrode active material is LiNi x Co y Mn 1-x-y O 2 , where 0.5≤x≤0.7, 0≤y≤0.1.
[0021] In addition, an embodiment of the present application further provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned ternary positive electrode material.
[0022] Compared with the prior art, the ternary cathode material provided in the embodiment of the present application is formed by a step-by-step wet spraying process, wherein a lithium hydroxide solution is first wet-sprayed to form an inner lithium hydroxide coating layer, and then a phosphoric acid solution is wet-sprayed to form an outer phosphoric acid coating layer. During the secondary sintering process, the lithium hydroxide reacts with the transition metal in the inner core to form an ion channel, thereby increasing the lithium ion transmission rate and improving the rate performance of the ternary cathode material. The phosphoric acid reacts with the lithium hydroxide to form a uniform and dense lithium phosphate coating layer, thereby improving the structural stability of the ternary cathode material. Furthermore, the lithium phosphate can form a stable covalent bond structure with the transition metal in the inner core, thereby improving the thermal stability of the ternary cathode material during the cycle.
[0023] In addition, due to the step-by-step spraying of lithium hydroxide solution and phosphoric acid solution, a lithium ion concentration gradient is formed in the coating layer, which gradually increases from the outside to the inside of the coating layer in the radial direction, forming a gradient distribution of low lithium concentration on the outside and high lithium concentration on the inside. This lithium concentration gradient design can optimize the transmission efficiency of lithium ions, promote the rapid migration of lithium ions during the charge and discharge process, accelerate the diffusion of lithium ions inside the ternary cathode material, and reduce the thermal expansion coefficient between the core and the coating layer, avoiding structural damage caused by stress concentration, thereby improving the rate performance and cycle stability of the ternary cathode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A process flow chart of the method for preparing the positive electrode material provided in an embodiment of the present application.
[0025] Figure 2 This is a schematic diagram of the structure of the electrochemical device provided in an embodiment of the present application.
[0026] Figure 3 This is a scanning electron microscope image of the positive electrode material of Example 1 of the present application.
[0027] Figure 4 This is a scanning electron microscope image of the positive electrode material of comparative example 4 of the present application.
[0028] Figure 5 It is a comparison chart of the cycle capacity retention rate curves at 45°C of batteries prepared with the positive electrode materials in Example 1 of the present application and Comparative Examples 1-4. DETAILED DESCRIPTION
[0029] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0030] Ternary cathode materials have advantages such as good energy density, cycle stability and safety. However, ternary cathode materials are prone to structural changes and capacity decay during long-term use. In order to overcome the above problems, it is common to modify ternary cathode materials by surface coating. Specifically, the surface of ternary cathode materials is coated with protective substances or lithium-containing compounds to improve the stability and capacity of ternary cathode materials.
[0031] However, the inventors of this application have found that the existing coating technology is usually only performed on the surface of the ternary positive electrode material, so it is difficult to ensure the uniformity and density of the coating layer, which may affect the stability of the coating effect. In addition, the existing lithium supplementation technology may cause excessive deposition of lithium salts or lithium compounds by coating lithium salts or lithium compounds on the surface of the ternary positive electrode material, thereby adversely affecting the overall performance of the ternary positive electrode material.
[0032] To do this, see Figure 1 As shown, the present application embodiment provides a method for preparing a ternary positive electrode material, which specifically includes the following steps:
[0033] Step S1, mixing the ternary cathode material precursor with the lithium source and sintering once to obtain a core.
[0034] Specifically, the ternary cathode material precursor and the lithium source are mixed in a certain proportion and sintered at 750°C to 1000°C for 6h to 18h, and then crushed after cooling to obtain the inner core.
[0035] In some embodiments, the chemical book of the ternary cathode material precursor can be Ni x Co y Mn 1-x-y (OH) 2 , wherein 0.5≤x≤0.7, 0≤y≤0.1. It is understandable that the type of the ternary cathode material precursor includes but is not limited to the above range, and may also be other ternary cathode material precursors such as lithium nickel cobalt aluminum hydroxide.
[0036] In some embodiments, the lithium source may include at least one of lithium phosphate, lithium hydroxide, lithium nitrate, and lithium sulfate.
[0037] In some embodiments, the ratio of the molar number of lithium in the lithium source to the total molar number of transition metals in the ternary positive electrode material precursor can be (1.02~1.3):1, which is conducive to the full incorporation of lithium ions during the formation of the inner core, promotes the uniform distribution of lithium ions in the inner core, and improves the electrochemical performance and structural stability of the ternary positive electrode material.
[0038] In some embodiments, the chemical formula of the core can be LiNi x Co y Mn 1-x-y O 2 , wherein 0.5≤x≤0.7, 0≤y≤0.1, and LiNi 0.5 Co 0.1 Mn 0.4 O 2 or LiNi 0.68 Co 0.1 Mn 0.22 O 2 It is understandable that the types of the core include but are not limited to the above ranges, and the electrochemical performance can be optimized by changing the precursor of the ternary cathode material or adjusting the element composition to meet the needs of different battery applications.
[0039] Step S2, mixing the inner core with the lithium hydroxide solution by spray coating to obtain a first mixture having an inner lithium hydroxide coating layer.
[0040] Specifically, the lithium hydroxide solution is uniformly sprayed onto the surface of the inner core by wet spray coating to uniformly mix and coat the inner core, thereby obtaining a first mixture having an inner lithium hydroxide coating layer. Compared with dry coating, wet spray coating has a more uniform coating effect.
[0041] In some embodiments, the mixing method may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the lithium hydroxide solution with the kernel and promote the interaction between the two. It is understandable that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the lithium hydroxide solution and the kernel is acceptable.
[0042] In some embodiments, the mass ratio of lithium hydroxide to the core in the lithium hydroxide solution can be (0.001-0.02):1, which helps to improve the coating effect and optimize the thickness and performance of the inner coating layer of the ternary cathode material. The mass ratio of the lithium hydroxide solution to the core can further be (0.01-0.015):1, and can be 0.001:1, 0.005:1, 0.01:1, 0.015:1, 0.018:1 or 0.02:1, etc.
[0043] In some embodiments, the mixture of the spray-coated inner core and the lithium hydroxide solution may also be dried. Drying is beneficial to the rapid formation of the lithium hydroxide inner coating layer on the surface of the inner core to achieve a better step-by-step coating effect.
[0044] In some embodiments, the drying temperature may be 120°C to 250°C, and a suitable drying temperature helps to fully remove moisture and further promote the formation of the LiOH inner coating layer. The drying temperature may further be 200°C to 250°C, and may be 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C or 250°C, etc.
[0045] In some embodiments, the drying time may be 0.5 h to 1 h, which is conducive to sufficient drying of the coating layer. The drying time may further be 0.6 h to 1 h, and illustratively may be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h or 1 h, etc.
[0046] In some embodiments, the dry atmosphere can be oxygen or air, which is conducive to the formation of the LiOH coating layer. The dry atmosphere can further be an oxygen-enriched air atmosphere or a pure oxygen atmosphere.
[0047] Step S3, mixing the first mixture with the phosphoric acid solution by spray coating to obtain a second mixture having an outer coating layer of phosphoric acid.
[0048] Similar to step S2, the phosphoric acid solution is uniformly sprayed onto the surface of the first mixture by wet spray coating to perform uniform mixing and coating. Compared with dry coating, the coating effect of wet spray is more uniform.
[0049] In some embodiments, the mixing method may include mixing, stirring or grinding with a high-speed mixer, etc., which can effectively mix the phosphoric acid solution and the dry material and promote the interaction between the two. It is understandable that the mixing method includes but is not limited to the above method, and any method that can achieve mixing of the phosphoric acid solution and the dry material is acceptable.
[0050] In some embodiments, the mass ratio of the phosphoric acid solution to the core can be (0.001-0.02):1, which helps to improve the coating effect and optimize the thickness and performance of the outer coating layer of the ternary cathode material. The mass ratio of the phosphoric acid solution to the core can further be (0.01-0.015):1, and can be 0.001:1, 0.005:1, 0.01:1, 0.015:1, 0.018:1 or 0.02:1, etc.
[0051] In some embodiments, the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is (0.78-2.1):3, which is conducive to optimizing the reaction process of phosphoric acid and lithium hydroxide. The molar ratio can further be (0.8-2.05):3, and can be exemplarily 0.78:3, 0.8:3, 0.85:3, 0.9:3, 0.95:3, 1:3, 1.05:3 or 1.1:1, etc.
[0052] Step S4, secondary sintering the second mixture to form a coating layer containing lithium phosphate on the surface of the inner core to obtain the ternary positive electrode material, wherein the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer.
[0053] Specifically, the second mixture is placed in a certain sintering atmosphere for secondary sintering. During the secondary sintering process, the LiOH sprayed in step S2 reacts deeply with the transition metal in the core and infiltrates, and the H sprayed in step S3 reacts deeply with the transition metal in the core. 3 PO 4 React with the LiOH sprayed in the remaining step S2 to finally form a uniform and dense Li 3 PO 4 The coating layer has a concentration gradient of lithium ions that gradually increases from the outside to the inside of the coating layer. 3 PO 4 The coating layer has a good isolation effect and can effectively reduce the side reactions between the ternary positive electrode material and the electrolyte, thereby extending the cycle life of the ternary positive electrode material.
[0054] Among them, deep reaction means that LiOH can undergo ion exchange or chemical reaction with transition metal ions to form new compounds or complexes. This reaction not only strengthens the binding force between the coating layer and the core, but also may improve the electrochemical properties of the material by forming different phases or compounds. For example, LiOH may form lithium nickel oxide with nickel, further improving the conductivity and stability of the ternary cathode material.
[0055] Infiltration refers to the phenomenon of mutual penetration of LiOH and the inner core. During the secondary sintering process, LiOH penetrates into the microscopic pores or surface layer of the inner core, forming a tighter bonding interface and promoting the formation of ion channels. After infiltration, lithium ions not only cover the surface of the inner core, but also penetrate into the inner core, forming a more efficient ion conduction channel, thereby significantly improving the ion transmission efficiency of the ternary cathode material and ultimately improving the rate performance of the ternary cathode material.
[0056] In addition, the LiOH inner coating layer reacts chemically with the phosphoric acid outer coating layer to generate Li 3 PO 4 This reaction process, through the ion exchange mechanism, makes Li + With PO 4 3- Combined with each other, a uniform phosphate coating is formed, which has good stability and density. The chemical bonding between the phosphate group and the transition metal ions in the core produces a stable covalent bond structure. This chemical bonding not only improves the adhesion of the coating, but also enhances the overall structural stability of the ternary cathode material; Li 3 PO 4 The formation of the coating layer also significantly improves the thermal stability and cycle stability of the ternary positive electrode material. Under high temperature conditions, the performance of the ternary positive electrode material is stable.
[0057] The concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer, which is conducive to further improving the transmission efficiency of lithium ions. The coating layer can also effectively reduce the thermal expansion coefficient between the core and avoid structural damage caused by stress concentration, thereby improving the structural stability of the ternary positive electrode material. The low lithium concentration in the outer layer can further reduce the interfacial side reactions between the ternary positive electrode material and the electrolyte, and the high lithium concentration in the inner layer provides sufficient lithium ions to meet the high energy requirements of the ternary positive electrode material, thereby improving the rate performance and cycle stability of the ternary positive electrode material.
[0058] In some embodiments, the secondary sintering atmosphere can be oxygen or air. The atmosphere of oxygen or air is conducive to maintaining the oxidation state of the metal ions in the ternary cathode material and promoting the Li 3 PO 4 , so that 3 PO 4 The coating layer is more uniform and dense. The atmosphere of the secondary sintering can further be an oxygen-enriched air atmosphere or a pure oxygen atmosphere.
[0059] In some embodiments, the temperature of the secondary sintering can be 300°C to 500°C. A higher sintering temperature is conducive to forming a dense coating layer and promoting a tighter combination between the coating layer and the core. The temperature of the secondary sintering can further be 400°C to 500°C, and can be 300°C, 350°C, 400°C, 450°C or 500°C, etc.
[0060] In some embodiments, the secondary sintering time may be 6 h to 18 h, which is conducive to the formation of the coating layer. The secondary sintering time may further be 10 h to 18 h, and may be 6 h, 8 h, 10 h, 12 h, 14 h, 16 h or 18 h, etc.
[0061] Compared with the prior art, the preparation method of the ternary positive electrode material provided in the embodiment of the present application has the following beneficial effects:
[0062] 1. Through the wet spray coating process, the effect of uniform coating on the surface of the inner core can be achieved, which is beneficial to improve the uniformity and density of the coating layer.
[0063] 2. Formation of LiOH-H by step-wise wet spraying 3 PO 4 The process of the composite coating can form a lithium concentration gradient lithium phosphate coating layer with high adhesion, which is beneficial to increasing the lithium ion diffusion rate and reducing problems such as structural damage caused by stress concentration, thereby improving the electrochemical performance and structural stability of the ternary positive electrode material.
[0064] 3. The preparation method is simple and efficient, which is conducive to the large-scale production of ternary positive electrode materials and has excellent commercial prospects.
[0065] An embodiment of the present application also provides a ternary positive electrode material, which is prepared by the preparation method of the above-mentioned ternary positive electrode material. The ternary positive electrode material includes an inner core and a coating layer located on the surface of the inner core, wherein the inner core is a ternary positive electrode active material, the coating layer contains lithium phosphate, and the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer, which can effectively solve the problems of capacity attenuation and cycle performance deterioration of the ternary positive electrode material in high-voltage long-term cycle use scenarios.
[0066] On the one hand, Li 3 PO 4The lithium in the coating layer reacts deeply with the transition metal (such as Ni, Co or Mn) in the core of the ternary positive polarity material and undergoes infiltration. This process not only enhances the chemical bonding between the coating layer and the core, but also forms an efficient lithium ion transmission channel, allowing lithium ions to migrate more quickly during the charge and discharge process, reducing the resistance to charge transfer. The formation of these ion channels greatly improves the conductivity and ion transfer rate of the ternary positive electrode material, thereby significantly improving the rate performance of the ternary positive electrode material, allowing the prepared battery to maintain high efficiency and stability under high rate charge and discharge conditions.
[0067] On the other hand, Li 3 PO 4 The coating layer has high density and uniformity, forming a barrier on the surface of the ternary cathode material, which can effectively inhibit the intrusion of moisture and oxygen and reduce the side reaction with the electrolyte, thereby improving the stability and cycle performance of the ternary cathode material. In addition, through coordination, charge transfer or crystal structure compatibility, Li 3 PO 4 The phosphate groups in the ternary cathode material can also form a stable covalent bond structure with the transition metal ions in the core, further enhancing the thermal stability of the ternary cathode material, making its chemical properties more stable in high temperature environments and less prone to decomposition or structural changes. This means that during the charge and discharge cycle, the ternary cathode material can withstand higher temperature fluctuations without causing a significant decrease in performance.
[0068] In addition, the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer, forming a distribution with lower lithium concentration in the outer layer and higher lithium concentration in the inner layer. This lithium concentration gradient design can optimize the transmission efficiency of lithium ions and promote the rapid migration of lithium ions during the charge and discharge process. The low lithium concentration in the outer layer can further reduce the interfacial side reactions between the ternary cathode material and the electrolyte, while the high lithium concentration in the inner layer provides sufficient lithium ions to meet the high energy requirements of the ternary cathode material, thereby improving the rate performance and cycle stability of the ternary cathode material.
[0069] At the same time, the coating layer can effectively disperse the externally applied stress and reduce the structural damage of the coating layer caused by stress concentration. The lithium concentration gradient design can alleviate the transmission of mechanical stress and make the force evenly distributed during the charging and discharging process, thereby significantly improving the structural stability of the ternary positive electrode material, which not only enhances the stability of the ternary positive electrode material, but also prolongs its cycle life, improves the overall performance of the prepared lithium-ion battery, and meets the needs of high-efficiency batteries.
[0070] In some embodiments, the coating layer may have a thickness of 3 nm to 10 nm. Within the above range, the electrolyte can be effectively isolated and sufficient ionic conductivity can be provided.
[0071] In some embodiments, the chemical formula of the ternary positive electrode active material can be LiNi x Co y Mn 1-x-y O 2 , wherein 0.5≤x≤0.7, 0≤y≤0.1, and LiNi 0.5 Co 0.1 Mn 0.4 O 2 or LiNi 0.68 Co 0.1 Mn 0.22 O 2 It is understandable that the types of ternary positive electrode active materials include but are not limited to the above ranges.
[0072] See also Figure 2 As shown, the embodiment of the present application also provides an electrochemical device (such as a battery), the electrochemical device 100 includes a positive electrode sheet 10, a negative electrode sheet 20, a separator 30 and an electrolyte 40, wherein the positive electrode sheet 10 includes a positive electrode active material, and the positive electrode active material is the ternary positive electrode material as described above. The electrochemical device 100 prepared using the ternary positive electrode material has the advantages of high capacity, high cycle performance and high stability.
[0073] The above-mentioned ternary positive electrode material and its preparation method and electrochemical device are further described below through specific examples.
[0074] Example 1
[0075] Step 1: Ni 0.68 Co 0.10 Mn 0.22 (OH) 2 The mixture was mixed with lithium hydroxide, wherein the molar ratio of Li to the total content of transition metals in the ternary cathode material precursor was 1.05:1, and sintered once in a pure oxygen atmosphere at a temperature of 950°C for 16 hours to obtain a core LiNi 0.68 Co 0.1 Mn 0.22 O 2 .
[0076] Step 2: Mix the inner core and the lithium hydroxide solution in a high-speed mixer by spray coating, put them in an oven and dry them in a pure oxygen atmosphere at a drying temperature of 100° C. for 1 hour, and crush them to obtain a first mixture with an inner lithium hydroxide coating layer, wherein the mass ratio of lithium hydroxide to the inner core in the lithium hydroxide solution is 0.012:1.
[0077] Step 3: Mix the first mixture and the phosphoric acid solution in a high-speed mixer by spray coating to obtain a second mixture, wherein the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is 1:3.
[0078] Step 4: sinter the second mixture in a pure oxygen atmosphere at a sintering temperature of 450° C. for 10 h to obtain a ternary positive electrode material.
[0079] Example 2
[0080] The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that in step 3, the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is 0.8:3.
[0081] Example 3
[0082] The specific process of the preparation process refers to Example 1, and the difference from Example 1 is that in step 3, the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is 1.2:3.
[0083] Comparative Example 1
[0084] Step 1: Ni 0.68 Co 0.10 Mn 0.22 (OH) 2 The mixture was mixed with lithium hydroxide, wherein the molar ratio of Li to the total content of transition metals in the ternary cathode material precursor was 1.05:1, and sintered once in a pure oxygen atmosphere at a temperature of 950°C for 16 hours to obtain a core LiNi 0.68 Co 0.1 Mn 0.22 O 2 .
[0085] Step 2: Mix the inner core and lithium hydroxide powder in a high-speed mixer by dry coating to obtain a first mixture having an inner lithium hydroxide coating layer, wherein the mass ratio of lithium hydroxide to the inner core in the lithium hydroxide powder is 0.012:1.
[0086] Step 3: Mix the first mixture and the phosphoric acid solution in a high-speed mixer by spray coating to obtain a second mixture, wherein the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is 1:3.
[0087] Step 4: sinter the second mixture in a pure oxygen atmosphere at a sintering temperature of 450° C. for 10 h to obtain a ternary positive electrode material.
[0088] Comparative Example 2
[0089] Step 1: Ni 0.68 Co 0.10 Mn 0.22 (OH) 2 The mixture was mixed with lithium hydroxide, wherein the molar ratio of Li to the total content of transition metals in the ternary cathode material precursor was 1.05:1, and sintered once in a pure oxygen atmosphere at a temperature of 950°C for 16 hours to obtain a core LiNi 0.68 Co 0.1 Mn 0.22 O 2 .
[0090] Step 2: Mix the inner core, lithium hydroxide solution and phosphoric acid solution in a high-speed mixer by a one-step spray coating method to obtain a mixture, wherein the mass ratio of lithium hydroxide in the lithium hydroxide solution to the inner core is 0.012:1, and the molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is 1:3.
[0091] Step 3: sinter the mixture in a pure oxygen atmosphere at a sintering temperature of 450° C. for 10 h to obtain a ternary positive electrode material.
[0092] Comparative Example 3
[0093] Step 1: Ni 0.68 Co 0.10 Mn 0.22 (OH) 2 The mixture was mixed with lithium hydroxide, wherein the molar ratio of Li to the total content of transition metals in the ternary cathode material precursor was 1.05:1, and sintered once in a pure oxygen atmosphere at a temperature of 950°C for 16 hours to obtain a core LiNi 0.68 Co 0.1 Mn 0.22 O 2 .
[0094] Step 2: Spray coating the core with Li 3 PO 4 The solution was mixed in a high-speed mixer to obtain a mixture in which Li 3 PO 4 The mass ratio to the core is 0.012:1.
[0095] Step 3: sinter the mixture in a pure oxygen atmosphere at a sintering temperature of 450° C. for 10 h to obtain a ternary positive electrode material.
[0096] Comparative Example 4
[0097] Step 1: Ni 0.68 Co0.10 Mn 0.22 (OH) 2 The mixture was mixed with lithium hydroxide, wherein the molar ratio of Li to the total content of transition metals in the ternary cathode material precursor was 1.05:1, and sintered once in a pure oxygen atmosphere at a temperature of 950°C for 16 hours to obtain a core LiNi 0.68 Co 0.1 Mn 0.22 O 2 .
[0098] Step 2: Dry coating the core LiNi 0.68 Co 0.1 Mn 0.22 O 2 With Li 3 PO 4 The powders were mixed in a high-speed mixer to obtain a mixture in which Li 3 PO 4 The mass ratio to the core is 0.012:1.
[0099] Step 3: sinter the mixture in a pure oxygen atmosphere at a sintering temperature of 450° C. for 10 h to obtain a ternary positive electrode material.
[0100] The following tests were performed on the ternary positive electrode materials obtained in Example 1 and Comparative Examples 1-4.
[0101] (I) The ternary cathode material prepared in Example 1 was observed by scanning electron microscopy. Figure 3 The ternary cathode material prepared in Comparative Example 4 was observed by scanning electron microscopy, and the results were as follows Figure 4 shown.
[0102] (ii) The electrical performance test conditions are as follows: the prepared positive electrode material, conductive carbon and binder polyvinylidene fluoride are mixed evenly in a mass ratio of 90:5:5 to form a button battery. The LAND battery testing system is used for constant current charge and discharge tests. During the test, the working voltage range of the first discharge capacity test is 2.8V~4.4V, the charge and discharge rate is +1C / -1C, and the CV cut-off current is 0.01C; the working voltage range of the 45°C cycle test is 2.8V~4.4V, the charge and discharge rate is +1C / 1C, and the CV cut-off current is 0.01C. The first coulomb efficiency at 1C, the first discharge capacity, and the capacity retention rate after 100 cycles at 45°C of the batteries prepared with the positive electrode materials obtained in Examples 1-3 and Comparative Examples 1-4 are measured. The results are shown in Table 1; Figure 5 It is a comparison chart of the 45°C cycle capacity retention rate curves of the corresponding batteries of Example 1 and Comparative Examples 1-4.
[0103]
[0104] The above results show that:
[0105] The surface morphologies of the ternary positive electrode materials after coating and sintering of Example 1 and Comparative Example 4 are compared. 3 PO 4 The particles attached to the surface of the inner core showed a distinctly rough morphology, whereas the surface of the particles after wet spray coating and sintering in Example 1 was relatively smooth, indicating that the wet spray coating effect was more uniform.
[0106] Comparative Example 1 is a dry coating of LiOH followed by a wet spraying of phosphoric acid solution to form Li 3 PO 4 Coating layer; Comparative Example 2 is LiOH and H 3 PO 4 One-step wet coating; Comparative Example 3 is Li 3 PO 4 Wet coating; Comparative Example 4 is Li 3 PO 4 Dry coating. Compared with Comparative Examples 1-4, from the comparative analysis of electrical properties, the ternary cathode material in Example 1 has the best performance in the first charge and discharge efficiency due to the step-by-step spray wet coating technology, which is significantly higher than Comparative Examples 1-4. In addition, due to the better uniformity and conductivity of the coating layer of the ternary cathode material in Example 1, after 100 cycles, its capacity retention rate is better than that of Comparative Examples 1-4, especially compared with the dry coating Li 3 PO 4 The comparative example 1 was increased by 4.17%, and the long-term life of the ternary positive electrode material in Example 1 was significantly improved.
[0107] The ternary positive electrode materials obtained in Examples 1-3 form a coating layer due to step-by-step wet spray coating, and the coating effect and electrochemical test results are excellent, indicating that the rate performance and stability of the ternary positive electrode materials provided in the examples of the present application in the long-term cycle process are improved.
[0108] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a ternary positive electrode material, characterized in that: include: The ternary cathode material precursor is mixed with a lithium source and sintered once to obtain a core; The core is mixed with a lithium hydroxide solution by spray coating and dried to obtain a first mixture having a lithium hydroxide inner coating layer; Mixing the first mixture with a phosphoric acid solution by spray coating to obtain a second mixture having an outer coating layer of phosphoric acid; and The second mixture is sintered for a second time to form a coating layer containing lithium phosphate on the surface of the inner core to obtain the ternary positive electrode material, wherein the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer.
2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The mass ratio of lithium hydroxide to the core in the lithium hydroxide solution is (0.001-0.02):
1.
3. The method for preparing the ternary cathode material according to claim 1, characterized in that: The mass ratio of phosphoric acid in the phosphoric acid solution to the core is (0.001-0.02): 1; The molar ratio of phosphoric acid in the phosphoric acid solution to lithium hydroxide in the lithium hydroxide solution is (0.78-2.1):
3.
4. The method for preparing a ternary positive electrode material according to claim 1, characterized in that: In the step of subjecting the second mixture to secondary sintering, the secondary sintering temperature is 300° C. to 500° C., and the secondary sintering time is 6 h to 18 h.
5. The method for preparing the ternary cathode material according to claim 1, characterized in that: The drying temperature is 150° C. to 250° C., and the drying time is 0.5 h to 1 h.
6. The method for preparing a ternary cathode material according to claim 1, characterized in that: The chemical formula of the ternary cathode material precursor is LiNi x Co y Mn 1-x-y (OH)2, where 0.5≤x≤0.7, 0≤y≤0.
1.
7. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the preparation method of any one of claims 1 to 6, wherein the ternary positive electrode material comprises an inner core and a coating layer located on the surface of the inner core, wherein the inner core is a ternary positive electrode active material, the coating layer contains lithium phosphate, and the concentration gradient of lithium ions in the coating layer gradually increases radially from the outside to the inside of the coating layer.
8. The ternary cathode material according to claim 7, characterized in that: The thickness of the coating layer is 3nm~10nm.
9. The ternary cathode material according to claim 7, characterized in that: The chemical formula of the ternary positive electrode active material is LiNi x Co y Mn 1-x-y O2, where 0.5≤x≤0.7, 0≤y≤0.
1.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is a ternary positive electrode material prepared by the preparation method of the ternary positive electrode material as described in any one of claims 1 to 6 or a ternary positive electrode material as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Method for producing positive electrode active material for lithium ion secondary batteries
WO2012176903A1